The Role for Epigenetic Modifications in Pain and Analgesia Response. (20th October 2013) - Lessans, Sherrie; Dorsey, Susan G.
Abstract : Pain remains a poorly understood and managed symptom. A limited mechanistic understanding of interindividual differences in pain and analgesia response shapes current approaches to assessment and treatment. Opportunities exist to improve pain care through increased understanding of how dynamic epigenomic remodeling shapes injury, illness, pain, and treatment response. Tightly regulated alterations of the DNA-histone chromatin complex enable cells to control transcription, replication, gene expression, and protein production. Pathological alterations to chromatin shape the ability of the cell to respond to physiologic and environmental cues leading to disease and reduced treatment effectiveness. This review provides an overview of critical epigenetic processes shaping pathology and pain, highlights current research support for the role of epigenomic modification in the development of chronic pain, and summarizes the therapeutic potential to alter epigenetic processes to improve health outcomes.